2014
DOI: 10.1002/j.0022-0337.2014.78.2.tb05672.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracurricular Factors Influence Perceived Stress in a Large Cohort of Colombian Dental Students

Abstract: The aim of this study was to investigate the association of extracurricular factors including socioeconomic status and career choice with perceived stress in dental school in a large cohort of Colombian dental students. Participants in the study were 5,700 students enrolled in seventeen Colombian dental schools. The study employed a Spanish adaptation of the Dental Environment Stressors (DES30-Sp) questionnaire and recorded an array of demographic, socioeconomic, career choice, and dental studies-related infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
6
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
(76 reference statements)
5
6
0
2
Order By: Relevance
“…Students in clinical phase perceived stress 2.25 times more than student in the basic sciences' phase. This result is in compliance with the findings of some other studies ( 33 , 34 ).…”
Section: Discussionsupporting
confidence: 94%
“…Students in clinical phase perceived stress 2.25 times more than student in the basic sciences' phase. This result is in compliance with the findings of some other studies ( 33 , 34 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, a lower subjective SES was associated with higher PSS-scores, which is in line with other reports [54,55]. In 2007, Taiwanese researchers found that medical students whose mothers had a lower SES reported a higher stress [54].…”
Section: Discussionsupporting
confidence: 92%
“…In 2007, Taiwanese researchers found that medical students whose mothers had a lower SES reported a higher stress [54]. In 2012, a Colombian study also observed a significant association between a lower subjective SES and a higher level of psychological distress in a large cohort of dental students [55]. One may speculate that distal extracurricular factors, such as SES, are important and independent determinants of perceived stress in medical and dental students.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our finding of the high importance to religiosity needs to be viewed in the context that Libya is of predominantly Muslim faith, where it is customary to pray five times each day, and for public modesty, many/most women might wear loose traditional dress (abayas) covering the body and not revealing the silhouette, or at least a Hijab for their heads concealing the hair and neck. Similarly, the higher proportion of females in the Libyan sample reflects what seems to be a reality at higher education institutions globally, and is in agreement with the gender distributions of university student samples from other higher income countries e.g., England, Wales and Northern Ireland, Sweden, Ireland, Korea [ 27 , 35 , 36 , 37 ], or lower income countries e.g., Colombia or Egypt [ 2 , 38 ]. We also agree with Iran, where across 300 students, 91% were single 71% lived in dormitories, 26% lived at home with their families and only 3% lived alone in rental properties [ 17 ].…”
Section: Discussionsupporting
confidence: 79%